Perspectives approach to the assessment of the quality of the vaccine plague live in terms of immunogenicity. Epidemiology and Vaccinal Prevention - S. E. Gostischeva; N. V. Abzaeva; E. L. Rakitina; D. G. Ponomarenko; M. V. Kostuchenko; O. V. Logvinenko; A. N. Kulichenko (Эпидемиология и вакцинопрофилактика, 2019)
Research objective – studying of a possibility of application antigen – stimulated cellular in vitro tests and technology of the cytometric analysis for control of immunogene activity of batches of vaccine plague live.Materials and methods. As biomodels used white laboratory mice, immunized commercial medicine of vaccine of the plague NIIEG line, live from a strain of Yersinia pestis EV, in doses – 8 х 102, 4 х 103, 2 х 104 and 1 х 105 of living microbic cells. Blood for a research was taken from intact mice and on 7, 14 and 21 days after immunization. The intensity of an antigenreaktivnost of lymphocytes was defined in cellular in vitro tests, analyzing a marker of early activation (CD45+CD3+CD25+) of lymphocytes with use of the monoclonal antibodies conjugated from fluorokhroma. As specific antigen used a complex of water-soluble antigens of a plague microbe.Results. As a result of a research it is shown that at the animals vaccinated by doses 4 х 103 – 1 х 105 living microbic cells, the highest level of an expression activation marker lymphocytes at anti-gene stimulation of in vitro is registered on 14 days after immunization, at the same time the quantity of CD25 – positive lymphocytes are on average 6.8 times higher, than in control group. High degree of direct link (coefficient of correlation of r = 1,000) quantities of the survived animals with increase in level of lymphocytes, expressiruyushchy markers of early activation – CD25 is established.Conclusions. The offered technique can be used as the additional test when studying degree of immunogenicity of new (kandidatny) vaccines against plague.